Cheng Ho and Islam in Southeast Asia - Chen, Dasheng (Institute of Southeast Asian Studies, 2009)
Tan Ta Sen has modestly suggested that, as a book to illustrate the peaceful impact of culture contact, he is concerned to show how such cultural influences not only led to transmissions, conversions and transferences involving Inner Asian Muslims from China and Yunnan Muslims, Chams, Javanese, Malays, Arabs and Indians, but also enabled many Chinese in the Malay world to retain their non-Muslim cultural traits.